The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.7314/apjcp.2014.15.22.9949
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Treatment Results in Soft Tissue Sarcomas of the Thoracic Wall Treated with Pre-or-Postoperative Radiotherapy - a Single Institution Experience

Abstract: Objective: To evaluate the long term results among patients with soft tissue sarcoma of the thoracic wall. Materials and Methods: Twenty-six patients who were treated with pre-or postoperative radiotherapy between December 1980-December 2007, with a diagnosis of soft tissue sarcoma of the thoracic wall were retrospectively evaluated. Results: The median age was 44 years (14-85 years) and 15 of them were male. A total of 50% of patients were grade 3. The most common histologic type of tumor was undifferentiated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 30 publications
(47 reference statements)
3
13
1
Order By: Relevance
“…Tsukushi et al ( 5 ) performed a study on 44 patients with chest wall STS involving a high proportion of dermatofibrosarcoma protuberans (27.2 vs. 7.5% in the current study), which rarely metastasizes and, therefore, may have resulted in the high 5-year OS rate of 89%. The distribution of histological subtypes in the series of Oksuz et al ( 4 ) was comparable with that in the patient population of the present study, resulting in similar 5-year OS rates (69 vs. 66%). The study by Oksuz et al ( 4 ) is the only analysis on chest wall STS to date that determined the prognostic effects of surgical margins.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Tsukushi et al ( 5 ) performed a study on 44 patients with chest wall STS involving a high proportion of dermatofibrosarcoma protuberans (27.2 vs. 7.5% in the current study), which rarely metastasizes and, therefore, may have resulted in the high 5-year OS rate of 89%. The distribution of histological subtypes in the series of Oksuz et al ( 4 ) was comparable with that in the patient population of the present study, resulting in similar 5-year OS rates (69 vs. 66%). The study by Oksuz et al ( 4 ) is the only analysis on chest wall STS to date that determined the prognostic effects of surgical margins.…”
Section: Discussionsupporting
confidence: 87%
“…The remaining studies on chest wall STS by Oksuz et al ( 4 ) and Tsukushi et al ( 5 ) revealed age and histological grade to be significant prognostic factors of survival based on univariate analyses. Tsukushi et al ( 5 ) performed a study on 44 patients with chest wall STS involving a high proportion of dermatofibrosarcoma protuberans (27.2 vs. 7.5% in the current study), which rarely metastasizes and, therefore, may have resulted in the high 5-year OS rate of 89%.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous retrospective studies have also focused exclusively on patients with primary chest wall STS; however, these studies are difficult to compare because of heterogeneous patient selection criteria and variable frequencies of high‐grade sarcomas (Table ). Nevertheless, these studies have identified several prognostic factors that influence survival in chest wall STS patients, including tumor grade, tumor size, completeness of surgical margins, and age . For example, Gross et al and Harati et al noted that a tumor size of <5 cm was associated with improved OS.…”
Section: Commentmentioning
confidence: 99%
“…Generally, wide local excision can be adequate for small superficial lesions. But, when the recurrence of tumor on the chest wall occurs, advanced cutaneous neoplasm and lymphoma, patients are not amenable to wide local excision with negative margins due to the bulk and extent of the tumor [2]. Meanwhile, radiotherapy to the chest wall could carry the risks of radiation-related toxicity such as pneumonitis, lung fibrosis, and coronary heart disease because considerable volumes of heart and lung are likely to receive high doses [2].…”
Section: Introductionmentioning
confidence: 99%
“…But, when the recurrence of tumor on the chest wall occurs, advanced cutaneous neoplasm and lymphoma, patients are not amenable to wide local excision with negative margins due to the bulk and extent of the tumor [2]. Meanwhile, radiotherapy to the chest wall could carry the risks of radiation-related toxicity such as pneumonitis, lung fibrosis, and coronary heart disease because considerable volumes of heart and lung are likely to receive high doses [2]. Although modern radiation therapy techniques have been introduced to avoid high dose exposure to surrounding and underlying healthy tissue, their clinical benefit is still a matter of debate [1].…”
Section: Introductionmentioning
confidence: 99%